Optimizing the placement of BLE transmitters for Indoor Positioning Systems - Pilski, Marek; Aleksandrowicz, Mateusz (Studia Informatica. System and information technology, 2023)
The article presents the results of experimental research related to the optimization of the placement of BLE transmitters (beacons) inside rooms in order to locate the user. The experiments were carried out to check how far BLE transmitters can be moved away from each other so that the average localization error was at a level acceptable to the user. The value of the localization error was assumed based on the literature (less than 1 m). As a result of the conducted experiments, a mathematical formula was defined to calculate the required number of BLE transmitters for the exact location inside the rooms. The experiments used BLE transmitters, rooms inside the building of Siedlce University of Natural Sciences and Humanities and a mobile application with a database. In the study of the optimization of the placement of beacons, the fingerprint technique was used.